#### Answer

- 6x - 4y = -12

#### Work Step by Step

3x + 2y = 6 multiply by -2 to both sides
-2 ( 3x + 2y ) = $-2\times6$
- 6x - 4y = -12

Published by
Pearson

ISBN 10:
0321726391

ISBN 13:
978-0-32172-639-1

- 6x - 4y = -12

3x + 2y = 6 multiply by -2 to both sides
-2 ( 3x + 2y ) = $-2\times6$
- 6x - 4y = -12

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.